Gargantua and Pantagruel - Rabelais, François.; Urquhart, Thomas; Motteux, Peter Anthony (London : Evermans, 1994)
"First published in four volumes between 1532 and 1552, Rabelais' comic masterpiece chronicles the adventures of a giant, Gargantua, and his son, Pantagruel. More than four centuries later, the terms "gargantuan" and "Rabelaisian" are synonymous with earthy humor, a surfeit of good food and drink, and pleasures of the flesh. This series of exaggerated fables was condemned upon its initial publication by the censors of the College de la Sorbonne. But beneath their bawdy, often scatological wit, the tales bear a deeper significance as the author's defense of daring and groundbreaking ideas. Using his ribald humor, Rabelais addresses timeless issues of education, politics, and philosophy. His parodies of classic authors as well as his own contemporaries offer a hilarious expose of human folly and an enduring satire of history, literature, religion, and culture. This edition features the classic translation by Sir Thomas Urquhart and Pierre le Motteux"--
Includes bibliographical references.
Keywords: FICTION / Classics; Humorous fiction